Upaya Sublimasi Diri Melalui Pelaksanaan Yajña Berbasis Catur Marga Bagi Mahasiswa Hindu Menurut Lontar Sundarigama - Oka Widana, Anak Agung Gde; Yundari, Anak Agung Istri Dalem Hana; Yutrisna, Gusti Ayu Dhea (Kamaya: Jurnal Ilmu Agama, 2024)
The implementation of yajña by the younger generation (Hindu students) often only refers to general "habits", while the use of specific references in the form of sacred lontar is still very minimal. Therefore, it is necessary to study more deeply the Hindu Sacred Lontar, especially for and by Hindu students in order to sublimate (change) the quality of understanding of religious values (yajña) to be more implementative. Translated with DeepL.com (free version). This research is a textual research, with the research method being descriptive qualitative and hermeneutic, so that in the analysis process it uses a qualitative in-depth verstehen (understanding) method. The approach used in this research is a psychological approach that focuses on literature. The primary data source in this research is Lontar Sundarigama which has been copied by Ida Bagus Arsana and published by PHDI Tabanan Regency, 1979. While the secondary data is from supporting books, literature reviews, documents, papers whose contents are relevant to the teachings of yajña. There are two data collection techniques used in this research, namely; Literature and Document recording. The results showed that self-sublimation efforts through Catur Marga-based yajña rituals for Hindu Students according to Lontar Sundarigama, consisted of; (1) Karma Marga (Students perform yajña regularly), (2) Bhakti Marga (Students place the aspect of Bhakti to God as an obligation), (3) Jnana Marga (Planting knowledge about good days for performing yajña), and (4) Raja Marga (collaboration in the implementation of yajña coupled with students' efforts to connect themselves to God through Yoga and Samadhi). Based on this study, it can be concluded that efforts to sublimate themselves through yajna for Hindu students have actually existed and been well expressed for a long time. Everything is clearly summarized in classical Hindu literature which can be used as a theoretical and implementative basis.